THE ROLE OF THE POLICE IN THE INVESTIGATION PROCESS AGAINST BUDGET DEVIATION VILLAGE SHOPPING USAGE (A Case Study on the Accountability Corruption of the Tanah Bersih APBDes in Tebing Syahbandar Ta. 2017) - Tomson Simanjuntak; Marzuki Marzuki; Yamin Lubis (Jurnal Ilmiah METADATA, 2021)
In investigating corruption, there are three institutions/ institutions that have the authority to conduct investigations, namely: police investigators, prosecutors and the Corruption Eradication Commission. In this study, the focus is on investigations conducted by police investigators. The formulation of the problem in this study is What is the role of the police in the investigation of irregularities in the use of village spending by the village head? What is the mechanism for investigating the deviation in the use of village expenditure by the Village Head? What are the obstacles and efforts of the investigator in conducting an investigation into the deviation of the budget for the use of village spending by the Village Head? This research is based on empirical juridical research, while the nature of the study is descriptive analysis. The data analysis used in this study is qualitative data analysis. Based on the results of the study, the role of the police in carrying out the investigation process against irregularities in the APBDes, relates to the authority possessed by the police in its position as a law enforcement agency that is part of the criminal justice system (criminal justice system) which by law is given the authority to conduct investigations of all criminal offenses, including those against alleged corruption. The investigation mechanism for irregularities in the use of village spending by the village head of Tanah Besi is based on community reports, which is in accordance with Police Report Number: LP/116/III/2019/SU/REST.HIGH/RESKRIM dated March 26, 2019. Investigators' obstacles in conducting investigations on the occurrence of irregularities in the use of village expenditure budget by the Village Head, including internal and external obstacles.